Pleural transudate: pathophysiology during superior vena cava syndrome. Issue 1 (25th February 2019) - Basille, Damien; Chevalier, Kevin; Andrejak, Claire; Jounieaux, Vincent
Pathophysiology, diagnosis and treatment of pleural transudates has widely been described in the literature [1–3]. Except for left heart failure, which requires diuretics, thoracoscopic talc pleurodesis appears to be a safe and effective therapeutic option [4–6]. We report the case of a woman who presented with a sudden pleural fluid formation from her parietal pleura during a talc pleurodesis for a recurrent transudative pleural effusion. We discuss the pathophysiology of this phenomenon. Pleural transudative effusion arises from imbalances between the hydrostatic and/or oncotic pressures. Temperature drop following talc poudrage through a spray may accentuate the pressure changes induced by superior vena cava syndrome. http://ow.ly/EpZm30nwVZj